Decision Making on Options for Development of Rest Area Facilities According to Highest And Best Use Using the Analytic Network Process Method (Case Study: Rest Area on Trans Sumatera Toll Road Tebing Tinggi–Parapat Section) - Hamdani Hamdani; Aswin Dewanto Hadisumarto (PT Mattawang Mediatama Solution, 2023)
The paper establishes and analyzes research regarding community needs for the concept of rest areas on the Trans Sumatra Toll Road Section of Tebing Tinggi - Parapat. The background of the research is due to the fact that the current planning of rest areas is still not effective yet in concept and does not pay much attention to the commercial aspect. Even though with the optimal commercial side of the rest area, the cost of maintaining the rest area can be funded from the income earned. Thus, the Company does not need to incur additional costs for maintenance, considering the Company's financial burden due to the construction of JTTS which is not financially feasible. The analysis used in this study is the Analytic Network Process (ANP) Model which will later be divided into 3 clusters namely the destination cluster, the criteria cluster, and the alternative cluster. The objective cluster is the final goal to be achieved in this study. Cluster criteria is the assessment criteria used in this study based on analysis of existing benchmark rest areas, literature studies, and expert validation. Alternative cluster is development options obtained from the results of the highest and best use analysis.